Mesenchymal Stem Cells in Restoration of Fertility at Experimental Pelvic Inflammatory Disease - Nataliia Volkova; Mariia Yukhta; Anatoliy Goltsev (Stem Cells International)
Inflammatory disorders account for a significant percentage of gynecologic diseases, particularly in women of reproductive age. It is known that stem cells have anti-inflammatory and regenerative properties. Based on this, we investigated the effect of intravenous administration of cryopreserved mesenchymal stem cells (cMSCs) of bone marrow on experimental chronic inflammation of the ovaries. The paper shows that on the 21st day after cMSC therapy, leukocyte infiltration of ovaries was slightly relative to the control group without treatment, and the ratio of developing and atretic follicles in the animals with cMSC injection dramatically increased, while in the control, it still remained on the side of atretic forms. The number of apoptotic oocytes after stimulation of superovulation in the control group was significantly higher (85.3 ± 5.2%) than that in the animals with therapy (5.7 ± 0.8%). Relative number of fertilized eggs in the group with cMSC therapy was higher by 40% compare to that in the control. Pregnancy rate in natural estrous cycle after cell administration increased by 20%, and average number of litters in this group was two times significantly higher than that in the control. So the intravenous injection of cMSCs has the restorative effect on the fertility at experimental pelvic inflammatory disease.